Environmental radiation in central zone of Peru - Manosalva Bacigalupo, Julio (2006)
From the discovery that low dose of radiation could produce effects on the human health, the study of the environmental radiation stopped to only be a scientific matter to become a problem of public health. Presently work, carried out in Julio’s months and August of the 2006 in the central area of the Peru, from the 0 to the 4800 meters on the level of the sea, two hundred fifty radiation measures have been obtained in twenty-five towns between Lima and Morococha, embracing five natural regions. The averages in opposing level of equivalent dose were, in the region Chala (0-500 meters of altitude), 240 nSv/h; in the region Yunga (500-2300 meters), 260,8 nSv/h; in the Quechua region (2300-3500 meters), 341.4 nSv/h; in the region Jalca (3500-4000 meters), 404,2 nSv/h; and the region Puna (4000-4800 meters), 515 nSv/h. The annual average in equivalent dose of the five regions was of 3,2 mSv, lightly bigger to the world average.